2021
DOI: 10.3390/ani11041029
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Plant-Based Bioactives Supplementation to Different Proportion of Concentrate Diets on Methane Production and Rumen Fermentation Characteristics In Vitro

Abstract: This In Vitro study was conducted to investigate the impact of plant-bioactives extract (PE), a combination of garlic powder and bitter orange extract, on methane production, rumen fermentation, and digestibility in different feeding models. The dietary treatments were 1000 g grass/kg ration + 0 g concentrate/kg ration (100:0), 80:20, 60:40, 40:60, and 20:80. The PE was supplemented at 200 g/kg of the feed. Each group consisted of 6 replicates. The experiment was performed as an In Vitro batch culture for 24 h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…However, the relationship between butyrate and methane emissions has not yet been clearly identified. Based on an in vitro study, Eslam et al 20 reported that supplementation with plant bioactive extracts reduced enteric methane and increased both ruminal propionate and butyrate concentrations. Another in vitro experiment reported that the methane reduction effect of resveratrol was affected by the rate of forage and concentrate, and the ruminal butyrate levels in resveratrol treatment differed according to dietary differences 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between butyrate and methane emissions has not yet been clearly identified. Based on an in vitro study, Eslam et al 20 reported that supplementation with plant bioactive extracts reduced enteric methane and increased both ruminal propionate and butyrate concentrations. Another in vitro experiment reported that the methane reduction effect of resveratrol was affected by the rate of forage and concentrate, and the ruminal butyrate levels in resveratrol treatment differed according to dietary differences 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of CH 4 and CO 2 were determined by injecting 1 mL of each sample into a gas chromatograph (GC-8A, Shimadzu Corp., Kyoto, Japan) using a gastight syringe (Hamilton Company, Reno, NV, USA). Further details on the GC condition were described previously [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Garlic ( Allium sativum ) has been applied pharmaceutically since ancient times in nearly every known civilisation, has been widely used as a foodstuff in the world, and is “generally recognized as safe” (GRAS) as a food flavouring agent by the U.S. FDA, making them ideal candidates to use as feed additives in livestock production [ 79 ]. However, plant-derived bioactive compounds also exhibit antimicrobial activity and, therefore, can affect the rumen microbial ecosystem directly [ 36 , 80 , 81 , 82 ].…”
Section: Garlic and Ruminant Ch 4 Emissionsmentioning
confidence: 99%